LINGUISTIC AND CULTURAL FEATURES OF THE CONCEPTS OF “NATIONALITY” IN ENGLISH AND UZBEK LITERATURE (TAMADDUN NURI JURNALI, 2024)
The article analyses the idea among the current subjects of modern linguistics. One of the key concepts in linguistic culture and cognitive linguistics is this word. The investigation of these two concept topic areas will be done in this essay. While “concept” is a broad term used in both linguistics and cognitive linguistics, it refers to two distinct notions in each field.